HUBUNGAN KECEPATAN DAN POWER OTOT TUNGKAI TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRI KELAS XI SMK NEGERI 3 TELUK KUANTAN - Egi Putra Arni; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to find out the correlation between the speed and power of leg muscles to the long jump squat style in female students of class XI of SMK Negeri 3 Teluk Kuantan. This research belongs to the type of correlational research. This study uses a total sampling technique, where all populations are sampled. Based on the determination of the sample above, a sample of 16 people was obtained. The results of this study indicate that there is a positive and significant corellation with correlation coefficient of r = 0.879, the meaning is 6.898 means tcount (6.898)> t table (2.145), H0 is rejected H1 is accepted. . for the corellation of leg muscle power variable to squat style long jump, there is a positive and significant relationship with correlation coefficient of r = 0.833, its significance is 5.633, means tcount (5.633)> t table (2.145), H0 is rejected H2 is accepted. and the corellation of the variable speed and power of leg muscles together to squat style long jump with a correlation coefficient of r = 0.890 where the meaning is tested by F-test and obtained fcount of 24.83, means tcount (24.83)> t table (3 , 80) thus H0 is rejected and Ha is accepted. Based on the results of research and data processing using the statistical procedures of the study, it was concluded that the variable speed and muscle power had a significant corellation to squat style long jump and could be applied to female students of SMK Negeri 3 Teluk Kuantan.Key Words: Speed, Power Of Leg Muscles, Long Jump